'Utilization of telemetry monitoring for non-cardiac conditions in non-critical patients: what are the trends and perceptions amongst medical residents?'. Issue 2 (3rd March 2020) - Fayyaz, Beenish; Rehman, Hafiz J.
ABSTRACT: Background & Objective: Current evidence shows that telemetry monitoring is commonly overutilized for ' non-cardiac' diseases such as COPD exacerbation, pneumonia, pulmonary embolism and sepsis. This issue has not been addressed clearly in the recent American Heart Association (AHA) guidelines and no standard recommendations on the use of telemetry in non-cardiac conditions exist; therefore, clinicians continue to make such decisions based on personal preferences. As medical residency is an important phase during which young physicians develop clinical skills and habits for their future practice, the aim of this study was to understand the prevalent trends related to inappropriate telemetry use amongst the medical residents at a community hospital and the associated factors which influence the use of telemetry monitoring in non-cardiac patients. Methods: All the residents undergoing internal medicine training at a community hospital were surveyed with the help of a questionnaire regarding the utility of telemetry in non-critical patients admitted with non-cardiac conditions. Results: Survey was completed by 37 residents. Analysis of the responses showed that despite the frequent use of telemetry in non-cardiac conditions, majority of the medical residents are unaware of the correct indications. Seventy-three percent choose 'continuous' telemetry when placing the order while only 16% (often or always) discontinue telemetry after 24 hours of uneventful use. Although 84% residents admitted that telemetry is overutilized, still 49% felt that it leads to better patient care while 70% considered it superior to frequent vitals monitoring for early detection of hemodynamic instability. Possible causes of inappropriate use included 'Lack of knowledge about the related literature' and 'Following trends set by the peers'. Conclusion: Majority of the medical residents overutilize telemetry in non-cardiac conditions due to lack of knowledge, perceived sense of security and inappropriate trends set by their colleagues. In order to abolish these tendencies, we propose the provision of adequate educational resources to the clinical staff at every level along with other system-based strategies.